Socioeconomic determinants and metabolic syndrome: Results from the Isfahan Healthy Heart Program - Gharipour, Mojgan; Sadeghi, Masoumeh; Nouri, Fatemeh; Nezafati, Pouya; Qader, Saleem S.; Taheri, Marzieh; Maghroun, Maryam; Abdalvand, Ali; Soleimani, Bahram; Sarrafzadegan, Nizal (Acta Biomedica Atenei Parmensis, 2017)
Introduction: The prevalence of metabolic syndrome (MetS) is increasing in Iran. We assessed the relationship between socioeconomic status (SES) and Mets components in the Iranian population. Materials and Methods: The sample for this study comprised a random cross-section of men and women from two province districts who participated in the Isfahan Healthy Heart Program (IHHP) in 2007. Each participant completed a questionnaire, underwent anthropometric testing and blood pressure measurements, and provided a blood sample. Mets was defined based on ATPIII criteria. Several SES dimensions, such as education, occupation, and number of children, as well as home, car, and personal computer ownership, were assessed to determine the participant’s SES. Results: A higher-than-average income, car ownership, owning or renting a private home, and having a computer are increasing towards increment in SES. All MetS components were more prevalent in participants defined as having a lower SES, while low HDL levels were more common in participants having an SES II (P>0.001). A multivariate analysis showed that having the lowest SES (I) increased the risk of MetS by 1.72 [1.44-2.07], whereas subjects having an SES III had a 1.23 [1.04-1.47] lower risk for MetS. Conclusions: The relationship between SES and Mets is due largely to behavioural factors, such as practicing unhealthy eating habits. Given the high prevalence of Mets in Iran, we propose that regular health check-ups may be useful in the early detection of the syndrome and, consequently, in the prevention of its effects. In addition, the early detection of MetS may result in the early diagnosis and prevention of cardiovascular diseases.